Aplicación de métodos no destructivos en la definición de propiedades del macizo rocoso (2015)
"The advances in the engineering projects associated with rocky media require more modern procedures every day to determine the mechanical properties of the subsoil, because the methods that have been implemented have lost their validity due to their exhaustion, delay, complexity and a high level of cost for its execution Non-Destructive Methods - MND, which uses elastic waves, have become an important tool for underground research because with its simplicity, speed and low cost, speed up the work, giving satisfactory results in the development With the application of this method it is possible to obtain indirectly the mechanical properties of the rock mass, however, the relationships that are used are still in the process of verification, as a contribution in the technical-scientific research process, in the present Some of the reasoning and procedures that allow the Give non-destructive methods a more practical application in the knowledge of the rock mass. In rock mechanics, the most representative mechanical parameters of the rocky medium are the simple compressive strength and the modulus of deformation. The MND, through the use of elastic waves that move in the rock mass, generated a very broad field of research, which is increasingly fertilized with the results that are produced and that are applied to the engineering of rocks. In the framework of the advanced investigation, the field works consisted of the execution of three perforations in rocky media formed by limestones, sandstones and arcillolites, respectively, obtaining the rock sampling to develop the laboratory program and additionally, tests were carried out Down Hole over the perforations by measuring the speed of elastic waves in the rocky massifs explored. "- Excerpt from the text